1929
DOI: 10.1002/zaac.19291800104
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zur Keramik hochfeuerfester Stoffe. l. Die Formen des Zirkondioxyds

Abstract: Die vorausgegangenen Mitteilungenl) hatten das Verhalten des ZrO, gegenuber anderen hochschmelzenden Oxyden in biniir e n Systemen zum Gegenstand, die nachstehende ,betrifft gleichartige t e r n a r e Systeme. Als zweite Komponente fand einerseits Tho,, das mit ZrO, zwei Mischkristalle und ein Entmischungsgebiet aufweist, andererseits BeO, das mit ZrO, keine Verbindung eingeht, neben CaO, MgO und CeO, als dritten Komponenten Verwendung. Experimentelles 50% ZrO, enthielten, wurden wie friiher mit einem Acetylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

1929
1929
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(34 citation statements)
references
References 9 publications
0
30
0
1
Order By: Relevance
“…X-ray diffraction examination on one specimen revealed that it was composed of a mixture of cubic crystals with several hexagonal SiC phases. It has been shown [17] that there are some 15 Groups III, IV, V, and VI would be "acceptable" on the basis of the low variation for the bulk density values gross effect^vill be that of a structural inlioinogeneity; (3) The segi'egation of grain sizes durmg fabrication [19]; and, (4) Roth [20] Analagous data for steel is not readily found. However, one study [21] gives the following results for specimens of "black sheet steel": V, for specimens cut in direction of rolling =2.…”
Section: Elastic Moduli a Methodsmentioning
confidence: 99%
“…X-ray diffraction examination on one specimen revealed that it was composed of a mixture of cubic crystals with several hexagonal SiC phases. It has been shown [17] that there are some 15 Groups III, IV, V, and VI would be "acceptable" on the basis of the low variation for the bulk density values gross effect^vill be that of a structural inlioinogeneity; (3) The segi'egation of grain sizes durmg fabrication [19]; and, (4) Roth [20] Analagous data for steel is not readily found. However, one study [21] gives the following results for specimens of "black sheet steel": V, for specimens cut in direction of rolling =2.…”
Section: Elastic Moduli a Methodsmentioning
confidence: 99%
“…It has been claimed by Ruff and Ebert [19], and Duwez, Brown, and Oelel [20] that SC20 3, Sm20 3, Gd20 3, and Y 20 3 all form cubic zirconia solid solutions. These conclusions have been quoted by Di etzel and Tober [2 1].…”
Section: Zirconatesmentioning
confidence: 96%
“…Patterns obtained at elevated temperaturcs wer e reported in Germany [5], but details of the furnace X-Ray Diffraction Apparatus are lacking. One factor that has prevented th e use of higher temperatures is the problem of cooling th e photographic film.…”
Section: Introductionmentioning
confidence: 99%